2022
DOI: 10.1007/s00401-022-02421-8
|View full text |Cite
|
Sign up to set email alerts
|

APOE4 exacerbates α-synuclein seeding activity and contributes to neurotoxicity in Alzheimer’s disease with Lewy body pathology

Abstract: Approximately half of Alzheimer’s disease (AD) brains have concomitant Lewy pathology at autopsy, suggesting that α-synuclein (α-SYN) aggregation is a regulated event in the pathogenesis of AD. Genome-wide association studies revealed that the ε4 allele of the apolipoprotein E (APOE4) gene, the strongest genetic risk factor for AD, is also the most replicated genetic risk factor for Lewy body dementia (LBD), signifying an important role of APOE4 in both amyloid-β (Aβ) and α-SYN pathogenesis. How APOE4 modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 71 publications
(85 reference statements)
0
28
0
Order By: Relevance
“…APOE4 has also been implicated in the progression of cognitive impairment or motor dysfunction within PD [54][55][56][57][58][59][60][61]. Recently, we reported that the presence of APOE4 gene allele exacerbates α-Syn seeding in a large AD cohort and a small cohort of LBD cases [62]. These findings indicate that APOE4 may potentially accelerate α-Syn aggregation and spreading during the disease [63].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…APOE4 has also been implicated in the progression of cognitive impairment or motor dysfunction within PD [54][55][56][57][58][59][60][61]. Recently, we reported that the presence of APOE4 gene allele exacerbates α-Syn seeding in a large AD cohort and a small cohort of LBD cases [62]. These findings indicate that APOE4 may potentially accelerate α-Syn aggregation and spreading during the disease [63].…”
Section: Discussionmentioning
confidence: 74%
“…Human iPSCs were differentiated into neurons as previously described [31,32]. Briefly, iPSCs were maintained in Matrigel (Corning, cat# 354277)-coated plates using mTeSR ™ 1 medium (Stemcell Technologies, cat# 85850).…”
Section: Differentiation Of Human Ipscs Into Neuronsmentioning
confidence: 99%
“…LB pathology is an additional neuropathological lesion found in approximately half of autopsy-confirmed AD patients [ 14 ]. Research has shown that APOE4 exacerbates the activity and neurotoxicity of α-synuclein, the primary constituent of LB pathology [ 15 ]. The objective of this study was to refine our previous findings by additionally adjusting for covariates (age, education, MMSE scores) and comparing neuropsychiatric symptom profiles between at-risk and not-at-risk females.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bassi et al demonstrated that amyloid-β (Aβ) deposits dramatically accelerate α-Syn pathogenesis and spread throughout the brain after injecting α-Syn preformed fibrils into mice with abundant Aβ plaques. Recent pathological studies in vitro showed that AD-related pathologies could exacerbates α-Syn seeding activity and neurotoxicity ( 43 , 44 ), suggesting an interaction between α-Syn pathology and AD-type pathologies in PD-CI.…”
Section: Pathological Characteristics Of Pd-cimentioning
confidence: 99%